COMPOSITE CARBON-DOTS AND PVA FOR SOLAR EVAPORATION APPLICATION - Fahrila Suci Ramadhani, Dinda
Solar evaporator technology is a technology that uses heating and evaporating water to produce clean water. TO improve the performance of solar evaporator, a solar evaporator with an interfacial method is used where the substrate in the form of polyvinyl alcohol (PVA) mixed with carbon-dots as a photothermal material is placed on the surface of the air to be evaporated. Carbon-dots product was synthesized from precursor materials in the form of citric acid and urea which were heated using microwaves. The aims of this study were to synthesize carbon-dots with PVA, and evaluate the performance of a solar evaporator with an interfacial system using CD/PVA/CA film as a solar absorber. The material characterization carried out was UV-Vis, FTIR, water solubility test, and photothermal tests. Based on UV-Vis tests conducted, carbon dots has a high absorbance in the UV to visible light region and this high absorbance is still obtained when the carbon dot is composited with PVA in the form of a film. The result of the water solubility test are used to determine the mechanical properties of the film where when the film is immersed, the film does not disintegrate and the carbon dot is not completely removed. In addition, there is the addition of citric acid (CA) to make a film that function as cross-link agents. FTIR test on CD/PVA/CA showed that there were hydroxyl, aldehyde, and carbonyl groups. The photothermal test with the interfacial system was carried out using a solar simulator with a light intensity of 1 kW/m2 (1 sun) resulting in an evaporation rate of 1.2 kg/m2 h and an efficiency of 75.33%.